Spatial-temporal lipidomics profile of acute myocardial injury. (3rd October 2022) - Huang, C; Mezger, S T P; Looi, W D; Muralidharan, S; Ji, S; Pastor, B C; Tan, S H; Charles, C J; Kofidis, T; Richard, A M; Chan, M Y; Torta, F T; et al.
Abstract: Background: Lipidome disturbance has long been recognized to occur after myocardial infarction (MI). Accumulation of excessive fatty acids induces production of reactive oxygen species and consequently deteriorates cardiac injury in MI. However, the spatial and temporal lipid profile in the heart following ischemic injury remains unknown. Purpose: We aim to uncover the temporal-spatial lipidome profile of the heart following ischemia reperfusion (I/R) injury and identify circulating lipids released from injured myocardium that are potentially useful for diagnosis of ischemic heart disease. Methods: C57/BL6 mice were subjected to 30 min myocardial ischemia followed by removal of the ligature to establish reperfusion injury. Porcine I/R injury was induced by 105 min myocardial ischemia followed by reperfusion. Human plasma was obtained from 143 post-MI patients. Myocardial lipid profiles were generated by matrix-assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MALDI-MSI) in different regions (infarct, remote and peri-infarct) at different time points. Moreover, the lipids in the heart and plasma were analysed by LC-MS/MS. Results: We observed a drastic alteration in the lipidome with distinct spatial-temporal features in the injured heart by both MALDI-MSI and LC-MS/MS. In the infarct heart tissue, as revealed by LC-MS/MS, we observed an elevation of glycerolipids that peaked at 3 hours after I/R, and a sustained elevation of phospholipids and sphingolipids up to 3 days. Similar alternations in lipid profile was observed but much weaker in the remote and peri-infarct heart tissue compared to the infarct tissue. Among those lipids, PC 32:0 detected by MALDI-MSI highly overlapped CD68 staining at a single-cell level, showing a strong correlation of PC 32:0 with macrophage infiltration in mouse hearts (R2=0.93, p<0.0001). A similar increase of PC 32:0 in the infarct area was also observed in porcine hearts following I/R injury. Surprisingly, plasma levels of PC 32:0 in the mice decreased after I/R injury. In humans, plasma levels of PC 32:0 in post-MI patients were lower than that in healthy individuals (p=0.03). Further analysis demonstrated that plasma levels of PC 32:0 determined within 72 hours after percutaneous coronary intervention were negatively correlated with the 6-month post-MI cardiac ejection fraction in patients (R2=0.08, p<0.001). Conclusions: A temporal-spatial lipidome profile was established in heart injury by synergizing LC-MS/MS and mass spectrometry imaging. PC 32:0 levels are positively correlated with myocardial macrophage infiltration but negatively correlated with cardiac function in cardiac I/R injury. Our findings indicate that PC 32:0 is a potential biomarker for cardiac injury and the inflammatory status in the injured heart. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Singapore Ministry of Health's National Medical Research Council